Molecular identification of Bambusa changningensis is the natural bamboo hybrid of B. rigida × Dendrocalamus farinosus - Zhuo, Juan; Vasupalli, Naresh; Wang, Yong; Zhou, Guoqiang; Gao, Huibin; Zheng, Ying; Li, Benxiang; Hou, Dan; Lin, Xinchun (Frontiers in Plant Science, 2023)
Bamboo is one of the fastest-growing plants commonly used in food, fibre, paper, biofuel, ornamental and medicinal industries. Natural hybridization in bamboo is rare due to its long vegetative period followed by gregarious flowering and death of the entire population. In the current study, a new bamboo species, Bambusa changningensis, shows intermediate characteristics of Dendrocalamus farinosus and B. rigida morphologically, but it is unknown whether B. changningensis is a natural hybrid. Moreover, B. changningensis has been identified as a superior variety of Sichuan Province with high pulping yield, fibre length and width. Therefore, we analyzed the morphological characteristics, DNA markers, DNA barcoding and chloroplast genomes to identify the hybrid origin of B. changningensis and possible maternal parent. We have developed the transcriptomic data for B. changningensis and mined the SSR loci. The putative parental lines and hybrid were screened for 64 SSR makers and identified that SSR14, SSR28, SSR31 and SSR34 markers showed both alleles of the parental species in B. changningensis, proving heterozygosity.Sequencing nuclear gene GBSSI partial regions and phylogenetic analysis also confirm the hybrid nature of B. changningensis. Further, we have generated the complete chloroplast genome sequence (139505 bp) of B. changningensis. By analyzing the cp genomes of both parents and B. changningensis, we identified that B. rigida might be the female parent. In conclusion, our study This is a provisional file, not the final typeset article identified that B. changningensis is a natural hybrid, providing evidence for bamboo's natural hybridization. This is the first report on confirming a natural bamboo hybrid and its parents through SSR and chloroplast genome sequence.